CoRoT 223992193: investigating the variability in a low-mass, pre-main sequence eclipsing binary with evidence of a circumbinary disk - Gillen, Edward; Aigrain, S.; Terquem, C.; Bouvier, J.; Alencar, S. H. P.; Gandolfi, Davide; Stauffer, J.; Cody, A.; Venuti, L.; Almeida, P. Viana; Micela, G.; Favata, F.; et al. (Astronomy and astrophysics, 2017)
CoRoT 223992193 is the only known low-mass, pre-main sequence eclipsing binary that shows evidence of a circumbinary disk. The system displays complex photometric and spectroscopic variability over a range of timescales and wavelengths. Using two optical CoRoT runs from 2008 and 2011/2012 (spanning 23 and 39 days), along with infrared Spitzer 3.6 and 4.5 μm observations (spanning 21 and 29 days, and simultaneous with the second CoRoT run), we model the out-of-eclipse light curves, finding that the large scale structure in both CoRoT light curves is consistent with the constructive and destructive interference of starspot signals at two slightly different periods. Using the vsini of both stars, we interpret this as the two stars having slightly different rotation periods: the primary is consistent with synchronisation and the secondary rotates slightly supersynchronously. Comparison of the raw 2011/2012 light curve data to the residuals of our spot model in colour-magnitude space indicates additional contributions consistent with a combination of variable dust emission and obscuration. There appears to be a tentative correlation between this additional variability and the binary orbital phase, with the system displaying increases in its infrared flux around primary and secondary eclipse. We also identify short-duration flux dips preceding secondary eclipse in all three CoRoT and Spitzer bands. We construct a model of the inner regions of the binary and propose that these dips could be caused by partial occultation of the central binary by the accretion stream onto the primary star. Analysis of 15 Hα profiles obtained with the FLAMES instrument on the Very Large Telescope reveal an emission profile associated with each star. The majority of this is consistent with chromospheric emission but additional higher velocity emission is also seen, which could be due to prominences. However, half of the secondary star’s emission profiles display full widths at 10% intensity that could also be interpreted as having an accretion-related origin. In addition, simultaneous u and r-band observations obtained with the MEGACam instrument on the Canada France Hawaii Telescope reveal a short-lived u-band excess consistent with either an accretion hot spot or stellar flare. The photometric and spectroscopic variations are very complex but are consistent with the picture of two active stars possibly undergoing non-steady, low-level accretion; the system’s very high inclination provides a new view of such variability.
Artikel-Nummer: A27
Gesehen am 17.08.2021